Composers : their lives and works. (DK Publishing, 2020)
"A compelling celebration of more than 90 of the world's most influential composers from the medieval period to the present day, Composers reveals the fascinating stories of their lives, loves, and works. Biographical entries - introduced with a stunning portrait of each featured composer - trace the friendships, loves, and rivalries that inspired each musical genius. Profiles offer revealing insights into what drove each individual to create the musical masterpieces - symphonies, concertos, and operatic scores - that changed the direction of classical music and are still celebrated and treasured today."--Amazon.com